O trivium como método propedêutico do ensino de filosofia no ensino médio - Jerônimo, Serginei Vasconcelos (2011)
This work aims to rescue a teaching method widespread in the Middle Ages, the trivium (logic, grammar and rhetoric) starting from the current reality of Brazilian education focused on philosophy. Our students are doing very poorly in the tests produced by the MEC, as have many difficulties in reading and writing. Without this problem solved teaching philosophy also becomes impossible. Since this subject is present in a mandatory national curriculum, we have this debate on how their teaching is possible and from where. We propose the trivium as a method in this work and make a whole path of the lifting of the problem faced by teachers of philosophy to a possible solution. In the introduction I present data on tests performed by the MEC and the PISA, for students of basic education, focusing on (a) 8 th / 9, in general, and the State School Hortêncio Diniz (school where I work as a teacher philosophy), in a specific way. The first chapter presents the program guiding the MEC in relation to its assessment, and the three arts of the trivium that are in line with the program. In the second chapter, I explore historically the trivium, the method and the implications of using the trivium as a method for a liberal education and the teaching of philosophy. In the third chapter, I ask a "philosophical license" to reflect a little more the relation between philosophy and education.